Acute exercise and oxidative stress: a 30 year history - Fisher-Wellman, Kelsey (BioMed Central, 2009)
The topic of exercise-induced oxidative stress has received considerable attention in recent years, with close to 300 original investigations published since the early work of Dillard and colleagues in 1978. Single bouts of aerobic and anaerobic exercise can induce an acute state of oxidative stress. This is indicated by an increased presence of oxidized molecules in a variety of tissues. Exercise mode, intensity, and duration, as well as the subject population tested, all can impact the extent of oxidation. Moreover, the use of antioxidant supplements can impact the findings. Although a single bout of exercise often leads to an acute oxidative stress, in accordance with the principle of hormesis, such an increase appears necessary to allow for an up-regulation in endogenous antioxidant defenses. This review presents a comprehensive summary of original investigations focused on exercise-induced oxidative stress. This should provide the reader with a well-documented account of the research done within this area of science over the past 30 years.